New wine in old bottle: Exploring the Corruption-inefficiency nexus using endogenous stochastic frontier approach - Massimo Finocchiaro Castro; Calogero Guccio (ZBW - Leibniz Information Centre for Economics, 2023)
A large body of literature has analyzed the relationship between factors affecting institutional quality at local level and the efficiency of firms with a particular focus on the role of corruption. However, due to reverse causality, the endogeneity problem makes it difficult to identify the real effect of institutional factors at local level on firms' efficiency. This paper adopts a novel stochastic frontier methodology to examine the relationship between the quality of local institutions and production efficiency, under the arrangement that endogeneity is well addressed. Specifically, we use a panel stochastic frontier analysis that endogenizes production efficiency and allows us to robustly assess the effect of corruption at local level on firms' technical efficiency. For this purpose, the paper employs a large panel of Italian firms operating in the building sector from 2013 to 2019. The empirical findings reported in the paper indicate that the factor affecting the quality of local institutions affect firms' performance, with a preeminent role played by the rule of law and the control of corruption. Moreover, when controlling for endogeneity, the magnitude of the effects of institutional quality factors at local level increase significantly. Our findings are robust to alternative IV strategies, alternative specifications of the production function, and inclusion of other factors that may affect firms' efficiency.
Keywords: D24; D73; L25; C23; C26; 330; Corruption; Firms; Production efficiency; Stochastic frontier analysis; Endogeneity